A Double-Blind, Placebo Controlled Trial, Evaluating the Effects of a Proprietary Blend of Plant Adaptogens on Sexual Satisfaction and Sexual Response in Adult Males - Lane, Gerry (Journal of Nutritional Therapeutics, 2014)
Introduction: Adaptogens are plant substances that offer resistance of the organism to stressors. The human genome is able to utilize these plant derived substance to increase cellular defense in-vivo. Previous studies which validated adaptogens benefit in athletic training and performance also demonstrated subjective reports of improved male sexual performance. It is the objective of this trial is to isolate and report the human male sexual response to a proprietary blend of adaptogens, androgenic herbs combined and select amino acids (Admax®/Potenter®) and compare it to placebo, over a 14 day period when compared to placebo. Methods: Subjects were randomized into two cohorts to compare study compound (n=42) with placebo (n=21). Exclusion criteria eliminated individuals with organic impotence and organic heart disease as well as those unable to give informed consent or unable to adhere to study protocol. Participants completed the International Index of Erectile Function (IIEF) prior to dosing and instructed to attempt sexual intercourse a minimum of twice per week during the study period. They also were instructed to complete a sexual satisfaction diary, which became part of the source documents upon completion of the trial. Each participant was provided 50 capsules of either study compound or placebo (8 capsules per day with 2 additional capsules). Participants completed the IIEF upon completion of the study as well. Results: 63 healthy adult males (age range 30-58, mean = 42.4, ± 3), were consented and enrolled in a placebo controlled, double blind, study of the male sexual experience and satisfaction in response to a proprietary blend of adaptogens (Admax/Potenter®). All participants completed the trial and submitted both pre & post self assessment utilizing the International Index of Erectile Function (IIEF). Participants on study compound (n=42) improved in all 5 measured parameters, compared to no change in the placebo group (n=21). All data was validated utilizing 2-tailed Student – T. Erectile function improved from 11.5 to 22.7 (p≤0.04) compared to placebo (decreased from11.7 to 10.8). Intercourse satisfaction improved from 5.6 to 11.1 (p≤0.05) compared to placebo (decreased from 5.5 to 5.2). Orgasmic function improved from 4.6 to 8.7 (p≤0.05) compared to placebo (increased from 4.7 to 4.8, not statistically significant). Sexual desire improved from 5.4 to 8.6 (p≤0.1) compared to placebo (decreased from 5.3 to 5.2). Overall sexual satisfaction improved from 3.1 to 9.1 (p≤0.01) compared to placebo (decreased from 3.3 to 2.9). Discussion: This data demonstrates that the male sexual experience is markedly enhanced with the utilization of this adaptogenic compound (Admax®/Potenter®), when taken 3-6 hours prior to anticipation of sexual intercourse. Subjectively, the data would also indicate that the effect is relatively short acting (lasting 6-24 hours) and moderate onset of action (taken 3-6 hours prior to event). Pharmacokinetic studies were not performed. There were no side effects reported by any of the participants as is consistent with its use in previous clinical trials. All early indications would suggests, that this proprietary blend of adaptogens is an excellent supplement to increase the male sexual experience and can safely be used up to 14 days without demonstrated side effects.